Synthetic Gene Circuits for Regulation of Next‐Generation Cell‐Based Therapeutics - Ana P. Teixeira; Martin Fussenegger (Advanced Science, 2024)
Abstract Arming human cells with synthetic gene circuits enables to expand their capacity to execute superior sensing and response actions, offering tremendous potential for innovative cellular therapeutics. This can be achieved by assembling components from an ever‐expanding molecular toolkit, incorporating switches based on transcriptional, translational, or post‐translational control mechanisms. This review provides examples from the three classes of switches, and discusses their advantages and limitations to regulate the activity of therapeutic cells in vivo. Genetic switches designed to recognize internal disease‐associated signals often encode intricate actuation programs that orchestrate a reduction in the sensed signal, establishing a closed‐loop architecture. Conversely, switches engineered to detect external molecular or physical cues operate in an open‐loop fashion, switching on or off upon signal exposure. The integration of such synthetic gene circuits into the next generation of chimeric antigen receptor T‐cells is already enabling precise calibration of immune responses in terms of magnitude and timing, thereby improving the potency and safety of therapeutic cells. Furthermore, pre‐clinical engineered cells targeting other chronic diseases are gathering increasing attention, and this review discusses the path forward for achieving clinical success. With synthetic biology at the forefront, cellular therapeutics holds great promise for groundbreaking treatments.